Smart blind stick - Haridass, Anbuselvam; Thanarajan, Shanti; Mohd Radzi, Syafiqah; Zulkiflli, Nur Amira; Abdullah, Fatin Aliah Phang; Nawi, Nina Diana; Yong Kang, Adam Wong; Mohd Muji, Siti Zarina; Pusppanathan, Jaysuman (UTHM Press, 2022)
This project aims to develop a simple and adaptable electronic guidance system for the blind and visually impaired, based on an embedded vision system with ultrasonic sensors. This system will help them navigate safely and independently, regardless of their environment. Vision impairment, also known as complete or near complete vision loss, can cause difficulties in reading and walking due to lack of equipment and training. Many people with visual impairments cannot independently move, requiring assistance from mobility specialists. Ultrasonic input, a technology using infrared signals to detect obstacles, has been developed to improve mobility.